Let the Car Drive You - Finocchi, Riccardo (E|C, 2023)
One of the most widespread technical and technological hybrid objects is undoubtedly the automobile, it is certainly a myth of today (like the Citroën Pallas Déesse mentioned by Barthes), it has entered social practices and contributed to defining complex semiotic systems of relations between objects. The automobile is a technical object that progressively replaces and/or simplifies human functions. With the introduction of artificial intelligence a crucial step begins, the car from being a refined prosthesis of human operations and functions moves to autonomy from driver control, becoming more and more visibly a hybrid object (in the sense defined by Latour as something mixed and metamorphic, transforming modes of existence), where human control is reduced to a minimum (and tends to be unnecessary in the future) These new full self-driving cars are truly mobile artificial intelligences capable of activating a complex system of mutual delegation between human and non-human agents, through a ‘subjectification’ of the car that configures new hybrids. This article highlights a system of sense relations from which emerges a tendency towards the neutralisation of human agentivity in the relationship between human beings and technical objects.